2011
DOI: 10.3109/13693786.2010.548084
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic significance ofAspergillusspecies isolated from respiratory samples in an adult pneumology ward

Abstract: Although the diagnostic significance of isolating Aspergillus spp. from respiratory cultures has been studied in immunocompromised hosts with invasive pulmonary aspergillosis (IPA), little is known of such infections in immunocompetent patients with other forms of aspergillosis. In this study of adult pneumology ward patients, we examined the association between Aspergillus spp. and disease prevalence. Laboratory records from April 1998 to March 2009 were reviewed to identify patients with Aspergillus spp. in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 37 publications
2
57
0
1
Order By: Relevance
“…This substantiated what has been reported by (12) 27.5%, (6) 22% and (22) 29% but it is higher than that obtained by (23) 4.8% and lower than recorded by (24) 45%. This discrepancy may be due to massive population growth and urban development which increased the prevalence of fungal infections in certain areas and putting more people at risk (25).…”
Section: IIIsupporting
confidence: 78%
“…This substantiated what has been reported by (12) 27.5%, (6) 22% and (22) 29% but it is higher than that obtained by (23) 4.8% and lower than recorded by (24) 45%. This discrepancy may be due to massive population growth and urban development which increased the prevalence of fungal infections in certain areas and putting more people at risk (25).…”
Section: IIIsupporting
confidence: 78%
“…colonization remains a matter of debate. In line with this hypothesis, it has been demonstrated that persistent colonization can induce an antibody response, and according to some authors, this seroconversion should prompt the reinforcement of patient monitoring and/or the start of antifungal therapy (20)(21)(22). The primary interest of including colonized patients in this evaluation is that they are typically those in whom Aspergillus serology is performed.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, repeated isolation of the same Aspergillus spp. or alternative diagnostic tests for invasive aspergillosis should be sought to accurately interpret a positive finding, especially in the absence of host factors (42). However, in the case of critically ill patients, an Aspergillus sp.-positive culture result portends a poor prognosis irrespective of colonization or active infection (43).…”
Section: Invasive Aspergillosismentioning
confidence: 99%